SAPHO Syndrome Masquerading as Metastatic Breast Cancer - Malik, Devin (Case Rep Rheumatol, 2018)
SAPHO syndrome is a rare clinical entity composed of synovitis, acne, pustulosis, hyperostosis, and osteitis (SAPHO). We describe a case of SAPHO syndrome masquerading as metastatic breast cancer in a patient with localized breast cancer who presented with cord compression. There was no pathologic evidence of metastatic cancer; however, a bone scan indicated osseous involvement. After multidisciplinary review of images and with additional findings of pustulosis and acne, a clinical diagnosis of SAPHO was made.